2000
DOI: 10.5006/1.3280519
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Stress Corrosion Cracking Susceptibility of Stainless Steels Based on Repassivation Kinetics

Abstract: Repassivation kinetics of rapidly scratched scars on the surface of type 304 (UNS S30400) stainless steel (SS) in a chloride solution was examined using an ampero-chronometric method. Its relationship to stress corrosion cracking (SCC) susceptibility measured by slow strain rate tests (SSRT) was explored. The repassivation kinetics was analyzed in terms of the current density flowing from the scratch (i[t]) as a function of the charge density that flowed from the scratch (q[t]). The log i(t) has a linear relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 14 publications
4
66
1
1
Order By: Relevance
“…It also agrees with the effect of alloying elements on the rate of the current change during the active-passive transition in Fig. 4 as well as the precious results on the effects of alloying elements on repassivation rate [21,[29][30][31]. In the meanwhile, cBV in the neutral pH solution was more sensitive to the alloying elements than in the acidic solution as listed in Table 2 though the trends in cBV with the alloying elements in the neutral pH solution are the same as those in the acidic solution in Fig.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…It also agrees with the effect of alloying elements on the rate of the current change during the active-passive transition in Fig. 4 as well as the precious results on the effects of alloying elements on repassivation rate [21,[29][30][31]. In the meanwhile, cBV in the neutral pH solution was more sensitive to the alloying elements than in the acidic solution as listed in Table 2 though the trends in cBV with the alloying elements in the neutral pH solution are the same as those in the acidic solution in Fig.…”
Section: Resultssupporting
confidence: 77%
“…In order to confirm the proportional relationship between cBV and protectiveness [21], the protectiveness of the passive film, whose thickness is inversely proportional to the protectiveness [34], was determined by measuring passive film thickness as shown in Fig. 9.…”
Section: Evaluation Of Protectiveness By Measuring Passive Film Thickmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of works concerning research into these aspects is considerable, with emphases in fracture morphology and electrochemical aspects within which the passive film and its rupture have been considered of utmost importance [1][2][3][4][5]. However, in spite of the vast amount of research efforts, the understanding of stress corrosion phenomena demands further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The factor α was the slope determined from log i(t) versus log t plot, which represented repassivation rate and approached to 1 7,8) . It was found that the film initially nucleated and grew according to the place exchange model 9,10) , and then grew according to the high electric field ion conduction model, in which log i(t) was linearly proportional to 1/q(t), where q(t) was charge density flowing from the bare surface [11][12][13] . This model assumed that all of current transients only contributed to passive film formation.…”
Section: Introductionmentioning
confidence: 99%